(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Bambusa vulgaris (Poaceae) is a bamboo species traditionally used for respiratory disorders and inflammation, but its multi-target potential against cystic bronchitis and thrombosis has not been examined using a combined phytochemical, in silico and in vitro approach. Methods: Ethanolic leaf extract, prepared by Soxhlet extraction, was screened phytochemically and profiled by GC–MS. Ten identified phytoconstituents were docked (auto docking standard precision) against five anti-thrombolytic and five anti-cystic-bronchitis protein targets. Thrombolytic activity was assessed by the in vitro clot lysis assay, and anti-inflammatory activity by protein denaturation inhibition, nitric oxide scavenging, and ferric ion reducing power assays. Results: GC–MS identified ten phytoconstituents. Cholestan-3-one, 4,4-dimethyl-, oxime showed the strongest multi-target binding across all cystic-bronchitis targets (NF-κB −7.3, COX-2 −10.2, TNF-α −8.5, iNOS −8.4, TLR4 −9.1 kcal/mol) and all thrombolytic targets (best: −8.9 kcal/mol vs Plasmin). The extract produced 47.3% clot lysis at 400 mg/mL and concentration-dependent anti-inflammatory activity, with IC₅₀ values of 398.51 μg/mL (protein denaturation), 435.80 μg/mL (nitric oxide scavenging), and 479.81 μg/mL (ferric reducing power). Conclusion: Combined GC–MS, docking and in vitro evidence supports Bambusa vulgaris leaf extract, and Cholestan-3-one, 4,4-dimethyl-, oxime in particular, as a multi-target plant-based candidate for cystic bronchitis and thrombotic disorders, warranting further in vivo and mechanistic validation.